(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
This article examines the reappropriation of traditional stories – myths, fairy tales, and epics – by second wave feminist artists, with a focus on Joan Jonas’s interdisciplinary work. Traditional stories have often been critiqued within feminism because of the way that they portray females and their fate in the plotlines. While there is immense variety within these genres, the stories are often perceived to be male-centric, where women are absent or only exist in service of the male protagonists’ stories. It is surprising then to find them as subject matter in the work of second wave feminists. Yet during this transformative period, marked by experimentation, activism, and self-actualization, feminist artists and writers drew heavily on these stories, exploring the tensions and possibilities they offered. Feminist artists, like Jonas, participated in the radical shift within the arts and the generation of new forms, specifically the proliferation of performance art. Influenced by poststructuralism, innovative interdisciplinary structures destabilized the meanings and illuminated the complexity and ambiguity of the stories. The diversity of approaches highlights the diversity of positions and sensibilities within second wave feminism and the many contradictions embedded in the movement, significantly influencing both contemporary art and contemporary society.